Effectiveness Improvement of the “Secondary Authorization” Rule in Criminal Law from the Perspective of Consequentialism - Wang, Zhelin (Transactions on Social Science, Education and Humanities Research, 2024)
Human flesh search engine accounts for a large proportion of cyber violence crimes, but a certain lag exists in the current criminal law regulations. There are some defects in regulating the subject of crime with deficiencies in the legislative provisions on the criminal behavior of personal information and the application of the “secondary authorization” rule. Hence, it is difficult to effectively exert the deterrent force that the criminal law should have. From the perspective of consequentialism, focusing on actively and passively disclosed personal information in human flesh search incidents, it can be found that passively disclosed personal information has a higher risk of cyberbullying and greater harm. In this regard, a public opinion identification mechanism should be put in place first to identify the tendency to cyberbullying in a timely manner. Before cyber violence makes a huge difference, all departments will jointly step down for rectification in accordance with relevant regulations. Secondly, criminal law is used to regulate, with the crime of "infringing on citizens’ personal information” mainly applicable. At the level of judicial practice, to avoid the dilemma of subjective knowledge, the “presumption and counter-evidence model” with lower cost and higher efficiency is used. Under this model, combined with the reasonable handling principle that “within a reasonable range, there is no major impact on personal rights and interests, and individuals do not choose to refuse”, all evidence and information are exhausted to solve problems that exceed the scope of fair use with a major impact and without having been authorized twice. Based on this model, it can effectively identify criminal suspects in human flesh search engines and improve the efficiency of criminal law regulation.